Menelusuri Jejak Kehidupan Keturunan Arab-Jawa di Luar Tembok Keraton Yogyakarta - Siti Hidayati Amal (Antropologi Indonesia, 2005)
The assimilation between Arabic in-migrants from Hadramaut with Javanese noble women has been taking place since the 13th century. Some of their offspring has identified themselves as Arabic Indonesians, especially after Independence, while a proportion of them have chosen to associate themselves with their local Javanese relatives. The latter even has lost their Arabic cultural identity, and as a result, has become Javanese. This article tries to explain why such a phenomenon has materialized using a family case of a Javanese trah-Javanese version of a clan-who has been living outside the Yogyakarta court. By tracing the family lineage; attitude -both culturally and politically- and life-style of certain trah's figures as Javanese in the context of larger meso-institutional and macro-structural systems, this article argues that the fading away of Arabic identity among the offspring of this particular trah could be attributed to two contextual political economic relations between the Dutch and the Javanese rulers in two different eras. The first one was before the Dipanegara war when the relation was mainly economic, namely the Dutch as the trade-corporate (VOC); and the second was afterwards during which time the Dutch managed to consolidate their full total-grip as a colonial power. Furthermore, this article argues that the attitude of the Dutch and the way they treated the offspring this particular Arabic-Javanese court families, and their generational impact, could only be understood within the larger contexts of the day. Key words: trade capitalism; social relation; political economic power.